2012
DOI: 10.29333/ejgm/82469
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress in Periodontitis

Abstract: Periodontitis is one of the most common oral infections induced

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
1
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 12 publications
1
24
1
2
Order By: Relevance
“…In a study by Epperlein et al [ 10 ], it was suggested that one of the main pathways to damage caused by the gas phase of cigarette smoke was through the NO and hydrogen peroxide interaction giving rise to an active molecule (which may be singlet oxygen) that can initiate lipid peroxidation, and red blood cell glutathione is one of the chief sources of protection against this damage. Another study by Dhotre et al [ 20 ] showed a significant increase in serum lipid peroxide and NO with a corresponding decrease in serum superoxide dismutase, glutathione peroxidase, and total antioxidant capacity in periodontitis patients. Further, it was noted that the oxidant levels were significantly higher and antioxidants were significantly lower in smoker patients than nonsmoker patients.…”
Section: Discussionmentioning
confidence: 99%
“…In a study by Epperlein et al [ 10 ], it was suggested that one of the main pathways to damage caused by the gas phase of cigarette smoke was through the NO and hydrogen peroxide interaction giving rise to an active molecule (which may be singlet oxygen) that can initiate lipid peroxidation, and red blood cell glutathione is one of the chief sources of protection against this damage. Another study by Dhotre et al [ 20 ] showed a significant increase in serum lipid peroxide and NO with a corresponding decrease in serum superoxide dismutase, glutathione peroxidase, and total antioxidant capacity in periodontitis patients. Further, it was noted that the oxidant levels were significantly higher and antioxidants were significantly lower in smoker patients than nonsmoker patients.…”
Section: Discussionmentioning
confidence: 99%
“…Periodontitis is a silent disease. It is an inflammatory response caused by groups of specific microorganisms in which the structural support to the tooth is destroyed (1,2) .…”
Section: Introductionmentioning
confidence: 99%
“…The markers, which have always been traditionally used and continue to be popular are estimation of malondialdehyde (TBARS assay), total antioxidant capacity or total antioxidant power, nitric oxide, antioxidant enzymes superoxide dismutase (SOD), catalase, glutathione peroxidase (GPx), glutathione reductase, Glutathione-S-Transferase, and estimation nonenzymatic markers like Vitamin C, Vitamin E, coenzyme Q, uric acid, bilirubin etc. [ 8 10 11 12 13 14 15 16 ]…”
Section: Introductionmentioning
confidence: 99%